Coagulation‐driven platelet activation reduces cholestatic liver injury and fibrosis in mice. (11th December 2014) - Joshi, N.; Kopec, A. K.; O'Brien, K. M.; Towery, K. L.; Cline‐Fedewa, H.; Williams, K. J.; Copple, B. L.; Flick, M. J.; Luyendyk, J. P.
Summary Background The coagulation cascade has been shown to participate in chronic liver injury and fibrosis, but the contribution of various thrombin targets, such as protease activated receptors (PARs) and fibrin(ogen), has not been fully described. Emerging evidence suggests that in some experimental settings of chronic liver injury, platelets can promote liver repair and inhibit liver fibrosis. However, the precise mechanisms linking coagulation and platelet function to hepatic tissue changes following injury remain poorly defined. Objectives To determine the role of PAR‐4, a key thrombin receptor on mouse platelets, and fibrin(ogen) engagement of the platelet αIIbβ3 integrin (αIIbβ3) in a model of cholestatic liver injury and fibrosis. Methods Biliary and hepatic injury was characterized following 4 week administration of the bile duct toxicant α‐naphthylisothiocyanate (ANIT) (0.025%) in PAR‐4–deficient mice, mice expressing a mutant form of fibrin(ogen) incapable of binding integrin αIIbβ3 (FibγΔ5), and wild‐type mice. Results Elevated plasma thrombin‐antithrombin and serotonin levels, hepatic fibrin deposition, and platelet accumulation in liver accompanied hepatocellular injury and fibrosis in ANIT‐treated wild‐type mice. PAR‐4 deficiency reduced plasma serotonin levels, increased serum bile acid concentration, and exacerbated ANIT‐induced hepatocellular injury and peribiliary fibrosis. Compared with PAR‐4–deficient mice, ANIT‐treated FibγΔ5 mice displayed more widespread hepatocellular necrosis accompanied by marked inflammation, robust fibroblast activation, and extensive liver fibrosis. Conclusions Collectively, the results indicate that PAR‐4 and fibrin‐αIIbβ3 integrin engagement, pathways coupling coagulation to platelet activation, each exert hepatoprotective effects during chronic cholestasis.